SHEEP BRUCELLOSIS IS A DANGEROUS DISEASE (LITERATURE REVIEW) (Academicia Globe: Inderscience Research, 2021)
Brucellosis Brucellosis is a chronic infectious disease characterized by abortion, placental abruption, endometritis, and reproductive disorders in animals. When brucellosis is detected on a farm, first of all, mass abortion (abortion) is observed in sheep, and a lot of money is spent on quarantine and rehabilitation of the farm. The main thing is that brucellosis is transmitted from animals to humans, and the economic damage from it becomes a major social problem.